Developing agent for bone cement, bone cement and preparation method thereof
Through the use of graphene-iodol composite structure developer, the problems of insufficient biocompatibility of traditional developers and the negative impact on the mechanical properties of bone cement are solved, and the effect of sufficient development, non-toxicity and improving the biological activity and mechanical properties of bone cement is achieved.
Patent Information
- Application Number
- CN202411909415.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-21
AI Technical Summary
Traditionally used in bone cement developer has insufficient biocompatibility, negatively affects the mechanical properties of bone cement, and may lead to wear and loosening of artificial joints.
The developer with a graphene-iodol composite structure is made of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent through an esterification reaction, and the composite structure formed is fully developed and is not toxic to the human body.
The developer is fully developed and is not toxic to the human body, improving the biological activity and mechanical properties of bone cement and overcoming the defects of traditional developer.
Smart Images

Figure BDA0005205247170000121 
Figure BDA0005205247170000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical materials, and in particular to a developer for bone cement, bone cement and a preparation method thereof. Background Art
[0002] Bone cement, also known as bone adhesive, is mainly used to fill defects and fix transplants. The developer is one of the important components of bone cement. Its main function is to make the bone cement fully visible to facilitate surgical observation.
[0003] There are many types of contrast agents, such as barium sulfate and zirconium dioxide. However, in clinical use, it is found that these traditional contrast agents have some defects: (1) biocompatibility is general, and long-term use, the heavy metal ions in the contrast agent may be toxic to the human body; (2) the addition of contrast agents has a negative impact on the mechanical properties of bone cement; (3) it may also cause wear and loosening of artificial joints.
[0004] In view of this, the present invention is proposed to solve at least one of the above technical problems. Summary of the invention
[0005] The first purpose of the present invention is to provide a developer for bone cement, which has sufficient development and is non-toxic to the human body. The use of the developer in bone cement can also improve the biological activity of bone cement and enhance the mechanical properties of bone cement.
[0006] The second object of the present invention is to provide a method for preparing the above-mentioned developer for bone cement.
[0007] The third object of the present invention is to provide a bone cement comprising the above-mentioned developer.
[0008] A fourth object of the present invention is to provide a method for preparing the above-mentioned bone cement.
[0009] In order to achieve the above object, the technical solution of the present invention is as follows:
[0010] The present invention provides a developer for bone cement, which has a graphene-iodine alcohol composite structure and is mainly made of the following raw materials:
[0011] Carboxylated graphene, iodine alcohol compounds, catalysts and dehydrating agents;
[0012] The molar ratio of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent is (9-10): (0.1-2.5): (0.3-0.6): (1.0-1.5).
[0013] Further, on the basis of the above technical solution of the present invention, the iodine alcohol compound includes any one of iohexol, iopamidol, ioversol, iobitrol or iodixanol, or a combination of at least two thereof;
[0014] Preferably, the carboxylated graphene has a thickness of 1-5 nm and a diameter of 1-3 um.
[0015] Further, on the basis of the above technical solution of the present invention, the dehydrating agent includes N,N'-dicyclohexylcarbodiimide and / or 1-ethyl-3 (3-dimethylpropylamine) carbodiimide;
[0016] Preferably, the catalyst comprises 4-dimethylaminopyridine or N-hydroxysuccinimide.
[0017] The present invention also provides a method for preparing the above-mentioned developer for bone cement, comprising the following steps:
[0018] The carboxylated graphene, the iodine alcohol compound, the catalyst and the dehydrating agent are mixed to carry out an esterification reaction, so as to obtain a developer for bone cement having a graphene-iodine alcohol composite structure.
[0019] Furthermore, the reaction temperature of the esterification reaction is 20 to 50° C., and the reaction time is 2 to 6 hours;
[0020] Furthermore, the preparation method also includes the step of: washing the esterification product with deionized water at room temperature after the esterification reaction, and then drying it at 50-60° C. for 2-3 hours to obtain the target product.
[0021] The present invention also provides a bone cement, comprising the following raw materials: a powder phase and a liquid phase; wherein the powder phase comprises the above-mentioned developer for bone cement;
[0022] Preferably, based on 100% by weight of the powder phase, the mass fraction of the developer in the powder phase is 9.0-11.0%.
[0023] Further, on the basis of the above technical solution of the present invention, the bone cement comprises a powder phase and a liquid phase, and the mass volume ratio of the powder phase to the liquid phase is 2.0-2.2 g:1 mL;
[0024] Based on the weight of the powder phase being 100%, the powder phase comprises the following components in mass fractions: 88.5-90.5% of polymethyl methacrylate, 0.4-0.6% of initiator and 9.0-11.0% of developer;
[0025] Taking the weight of the liquid phase as 100%, the liquid phase comprises the following components in mass fractions: 96.49-97.49% of methyl methacrylate, 2.5-3.5% of an accelerator and 0.009-0.011% of a retarder.
[0026] Further, on the basis of the above technical solution of the present invention, the bone cement comprises a powder phase and a liquid phase, and the mass volume ratio of the powder phase to the liquid phase is 2.0-2.2 g:1 mL;
[0027] Based on 100% by weight of the powder phase, the powder phase comprises the following components in mass fractions: 88.5-90.5% of polymethyl methacrylate, 0.4-0.6% of benzoyl peroxide and 9.0-11.0% of a developer;
[0028] Taking the weight of the liquid phase as 100%, the liquid phase comprises the following components in mass fractions: 96.49-97.49% of methyl methacrylate, 2.5-3.5% of N,N-dimethyl-p-toluidine and 0.009-0.011% of hydroquinone.
[0029] The present invention also provides a method for preparing the above-mentioned bone cement, comprising the following steps:
[0030] The powder phase and the liquid phase are mixed and solidified to obtain bone cement.
[0031] Compared with the prior art, the present invention has the following technical effects:
[0032] (1) The present invention provides a developer for bone cement, which is mainly made of raw materials such as carboxylated graphene, iodine alcohol compounds, catalysts and dehydrating agents. The obtained developer of graphene-iodine alcohol composite structure has sufficient development and is non-toxic to the human body. The use of this developer in bone cement can also improve the biological activity of bone cement and enhance the mechanical properties of bone cement, thereby overcoming the defects of traditional developers.
[0033] (2) The present invention provides a method for preparing the developer, which utilizes the characteristics of carboxylated graphene and iodine alcohol compounds to carry out an esterification reaction to obtain the developer. The preparation method is simple in process and easy to operate.
[0034] (3) The present invention provides a bone cement comprising the above-mentioned developer for bone cement. In view of the advantages of the above-mentioned developer, the bone cement containing the developer also has the same advantages.
[0035] (4) The present invention provides a method for preparing the above-mentioned bone cement, which is easy to operate. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be clearly and completely described below in combination with the implementation. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] According to a first aspect of the present invention, there is provided a developer for bone cement, which is mainly made of the following raw materials:
[0038] Carboxylated graphene, iodine alcohol compounds, catalysts and dehydrating agents;
[0039] The molar ratio of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent is (9-10): (0.1-2.5): (0.3-0.6): (1.0-1.5).
[0040] Carboxylated graphene is mainly obtained by carboxylating graphene. Carboxylated graphene has excellent mechanical properties, such as elasticity, flexibility, and adaptability to flat or undulating surfaces. These characteristics enable graphene to be used as a reinforcing material for bone cement to enhance the mechanical properties of bone cement.
[0041] There is no specific limitation on the source of the carboxylated graphene, which can be purchased from the market or prepared by itself.
[0042] Iodine alcohol compounds are non-ionic iodine developers, which have the characteristics of low contrast density, low toxicity, and good tolerance. However, since non-ionic developers are water-soluble substances, they circulate quickly with the blood in the body and are easy to adhere, resulting in the inability to develop for a long time. Therefore, iodine alcohol compounds are combined with carboxylated graphene to prepare a new contrast agent. Carboxylated graphene and iodine alcohol compounds are compounded through chemical reactions, and the developer state of the graphene-iodine alcohol composite structure obtained by the compounding is stable, which overcomes the defect that iodine alcohol compounds alone as developers cannot be used for long-term development.
[0043] Since the carboxylated graphene and the iodine alcohol compound are compounded through a chemical reaction (mainly an esterification reaction), the role of the dehydrating agent is mainly to remove the water generated during the reaction and promote the smooth progress of the reaction.
[0044] There are also certain restrictions on the amount of each raw material used. Typical but non-limiting molar ratios of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent are 9:0.1:0.3:1.0, 9.5:0.1:0.3:1.0, 10:0.1:0.3:1.0, 9:0.5:0.4:1.0, 9:1:0.5:1.2, 9:2:0.3:1, 9:2.5:0.5:1.5, 9.5:0.1:0.6:1.5, 9.5:0.5 : 0.4:1.0, 9.5:1:0.5:1.2, 9.5:2:0.3:1, 9.5:2.5:0.5:1.5, 9.5:0.1:0.6:1.5, 10:0.1:0.6:1.5, 10:0.5:0.4:1.0, 10:1:0.5:1.2, 10:2:0.3:1, 10:2.5:0.5:1.5, 10:0.1:0.6:1.5 or 10:2.5:0.6:1.5.
[0045] The term "mainly made of..." in the present invention means that in addition to the raw materials, other raw materials acceptable in the developer field may also be included, and these other raw materials may give the developer different properties. In addition, the term "mainly made of..." in the present invention may also be replaced by the closed form "made of" or "is".
[0046] The type of iodine alcohol compound directly affects the final properties of the developer. As a preferred embodiment of the present invention, the iodine alcohol compound includes any one of iohexol, iopamidol, ioversol, iobitrol or iodixanol, or a combination of at least two thereof.
[0047] As a preferred embodiment of the present invention, the dehydrating agent includes N,N'-dicyclohexylcarbodiimide and / or 1-ethyl-3 (3-dimethylpropylamine) carbodiimide.
[0048] It should be noted that the "and / or" here means that the dehydrating agent may include only N,N'-dicyclohexylcarbodiimide, only 1-ethyl-3 (3-dimethylpropylamine) carbodiimide, or include N,N'-dicyclohexylcarbodiimide and 1-ethyl-3 (3-dimethylpropylamine) carbodiimide.
[0049] The catalyst directly affects the reaction rate of the carboxylated graphene and the iodine alcohol compound. As a preferred embodiment of the present invention, the catalyst includes 4-dimethylaminopyridine or N-hydroxysuccinimide.
[0050] By limiting the specific types of iodine alcohol compounds, dehydrating agents and catalysts, it is possible to ensure that the clinical application performance of bone cement is not affected while ensuring good development performance when added to bone cement, while improving the mechanical properties of bone cement.
[0051] According to a second aspect of the present invention, there is also provided a method for preparing the above-mentioned developer for bone cement, comprising the following steps:
[0052] The carboxylated graphene, the iodine alcohol compound, the catalyst and the dehydrating agent are mixed to carry out an esterification reaction, so as to obtain a developer for bone cement having a graphene-iodine alcohol composite structure.
[0053] As a preferred embodiment of the present invention, the reaction temperature of the esterification reaction is 20 to 50° C., and the reaction time is 2 to 6 hours;
[0054] As a preferred embodiment of the present invention, the preparation method further comprises: after the esterification reaction, the esterification product is rinsed with deionized water at room temperature, and then dried at 50-60° C. for 2-3 hours to obtain the target product.
[0055] According to a third aspect of the present invention, there is also provided a bone cement comprising the following raw materials: a powder phase and a liquid phase; wherein the powder phase comprises the above-mentioned developer for bone cement.
[0056] In view of the advantages of the above-mentioned developer, the bone cement containing the developer also has the same advantages.
[0057] As a preferred embodiment of the present invention, based on 100% by weight of the powder phase, the mass fraction of the developer in the powder phase is 9.0-11.0%.
[0058] The typical but non-limiting mass fraction of the developer in the powder phase is 9.0%, 9.2%, 9.4%, 9.5%, 9.6%, 9.8%, 10.0%, 10.2%, 10.4%, 10.5%, 10.6%, 10.8% or 11.0%. If the amount of developer is too large (higher than 11%), it may cause the setting properties of the bone cement itself to change, affecting clinical application. If the amount of developer is too small (lower than 9%), it may cause the development effect to fail to meet the requirements, thus affecting its clinical application. Therefore, the amount of developer should be controlled within an appropriate range of values.
[0059] As a preferred embodiment of the present invention, bone cement is mainly made of the following raw materials: a powder phase and a liquid phase, and the mass volume ratio of the powder phase to the liquid phase is 2.0-2.2 g: 1 mL. The typical but non-limiting mass volume ratio of the powder phase to the liquid phase is 2.0 g: 1 mL, 2.1 g: 1 mL or 2.2 g: 1 mL.
[0060] As a preferred embodiment of the present invention, based on 100% by weight of the powder phase, the powder phase includes the following components in mass fractions: 88.5-90.5% of polymethyl methacrylate, 0.4-0.6% of initiator and 9.0-11.0% of developer.
[0061] Specifically, the typical but non-limiting mass fraction of polymethyl methacrylate is 88.5%, 89.0%, 89.5%, 90.0% or 90.5%. The typical but non-limiting mass fraction of the initiator is 0.4%, 0.45%, 0.5%, 0.55% or 0.6%. The typical but non-limiting mass fraction of the developer is 9.0%, 9.2%, 9.5%, 9.8%, 10.0%, 10.2%, 10.4%, 10.5%, 10.6%, 10.8% or 11.0%.
[0062] As a preferred embodiment of the present invention, based on 100% by weight of the liquid phase, the liquid phase comprises the following components in mass fractions: 96.49-97.49% of methyl methacrylate, 2.5-3.5% of an accelerator and 0.009-0.011% of a retarder.
[0063] Specifically, the typical but non-limiting mass fraction of methyl methacrylate is 96.49%, 96.5%, 96.60%, 96.80%, 97.00%, 97.10%, 97.20%, 97.40% or 97.49%. The typical but non-limiting mass fraction of the accelerator is 2.5%, 2.6%, 2.8%, 2.9%, 3.0%, 3.2%, 3.4% or 3.5%. The typical but non-limiting mass fraction of the retarder is 0.009%, 0.0092%, 0.0095%, 0.0098%, 0.01% or 0.011%.
[0064] By further limiting the amount of each raw material in the powder phase and liquid phase, the solidification and mechanical properties of bone cement meet the requirements of the standard YY0459 "Surgical Implants-Acrylic Resin Bone Cement", thereby ensuring its clinical application. At the same time, bone cement can also show good imaging performance.
[0065] As a preferred embodiment of the present invention, the bone cement comprises a powder phase and a liquid phase, and the mass volume ratio of the powder phase to the liquid phase is 2.0-2.2 g:1 mL;
[0066] Based on 100% by weight of the powder phase, the powder phase comprises the following components in mass fractions: 88.5-90.5% of polymethyl methacrylate, 0.4-0.6% of benzoyl peroxide and 9.0-11.0% of a developer;
[0067] Taking the weight of the liquid phase as 100%, the liquid phase comprises the following components in mass fractions: 96.49-97.49% of methyl methacrylate, 2.5-3.5% of N,N-dimethyl-p-toluidine and 0.009-0.011% of hydroquinone.
[0068] By further limiting the types and amounts of each raw material of bone cement, the setting and mechanical properties of bone cement meet the requirements of the standard YY0459 "Surgical Implants-Acrylic Resin Bone Cement", thus ensuring its clinical application. At the same time, bone cement can also show good imaging properties.
[0069] According to a fourth aspect of the present invention, there is also provided a method for preparing the above-mentioned bone cement, comprising the following steps:
[0070] The powder phase and the liquid phase are mixed and solidified to obtain bone cement.
[0071] The preparation method of the bone cement provided by the invention is simple and convenient to operate.
[0072] The present invention will be further described below in conjunction with specific embodiments and comparative examples.
[0073] Example 1
[0074] This embodiment provides a developer for bone cement, which is mainly made of the following raw materials:
[0075] Carboxylated graphene, iodine alcohol compounds, catalysts and dehydrating agents;
[0076] Among them, the molar ratio of carboxylated graphene, iodine hexanol (iodine alcohol compound), 4-dimethylaminopyridine (catalyst) and N,N'-dicyclohexylcarbodiimide (dehydrating agent) is 9:0.1:0.3:1.0.
[0077] The method for preparing the developer provided in this embodiment comprises the following steps:
[0078] (1) mixing carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent according to the molar ratio of this embodiment to carry out esterification reaction;
[0079] The reaction temperature of the esterification reaction is 30°C and the reaction time is 3h;
[0080] (2) The esterification product of step (1) is rinsed with deionized water at room temperature, and then dried at 50-60° C. for 2-3 hours to obtain a developer for bone cement having a graphene-iodine alcohol composite structure.
[0081] Example 2
[0082] This embodiment provides a developer for bone cement. Except that the iodine alcohol compound iohexol is replaced by iopamidol, the other raw materials, dosage and preparation method are the same as those in Example 1.
[0083] Example 3
[0084] This embodiment provides a developer for bone cement, except that the iodine alcohol compound iohexol is replaced by ioversol and iobitol (the molar ratio of ioversol to iobitol is 1:1), and the other raw materials, dosages and preparation methods are the same as those in Example 1.
[0085] Example 4
[0086] This embodiment provides a developer for bone cement, except that the iodine alcohol compound iohexol is replaced by iohexol and iodixanol (the molar ratio of iohexol to iodixanol is 1:1), and the other raw materials, dosages and preparation methods are the same as those in Example 1.
[0087] Example 5
[0088] This embodiment provides a developer for bone cement. Except that the molar ratio of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent is replaced with 9:2.5:0.3:1.0, the remaining raw materials, dosage and preparation method are the same as those in Example 1.
[0089] Example 6
[0090] This embodiment provides a developer for bone cement, except that the molar ratio of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent is replaced with 10:0.1:0.3:1.0, the remaining raw materials, dosage and preparation method are the same as those in Example 1.
[0091] Example 7
[0092] This embodiment provides a developer for bone cement, except that the molar ratio of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent is replaced with 10:2.5:0.6:1.5, the remaining raw materials, dosage and preparation method are the same as those in Example 1.
[0093] Example 8
[0094] This embodiment provides a developer for bone cement, except that the molar ratio of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent is replaced with 9.5:1:0.4:1.2, the remaining raw materials, dosage and preparation method are the same as those in Example 1.
[0095] Example 9
[0096] This embodiment provides a developer for bone cement, which is mainly made of the following raw materials:
[0097] Carboxylated graphene, iodine alcohol compounds, catalysts and dehydrating agents;
[0098] Among them, carboxylated graphene; iodixanol (iodine alcohol compound), 4-dimethylaminopyridine (catalyst); 1-ethyl-3 (3-dimethylpropylamine) carbodiimide (dehydrating agent);
[0099] The molar ratio of the carboxylated graphene, the iodine alcohol compound, the catalyst and the dehydrating agent is 9.2:2:0.5:1.4.
[0100] The method for preparing the developer provided in this embodiment comprises the following steps:
[0101] (1) mixing carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent according to the molar ratio of this embodiment to carry out esterification reaction;
[0102] The reaction temperature of the esterification reaction is 40°C and the reaction time is 4h;
[0103] (2) The esterification product of step (1) is rinsed with deionized water at room temperature, and then dried at 55° C. for 2.5 hours to obtain a developer for bone cement having a graphene-iodine alcohol composite structure.
[0104] Example 10
[0105] This embodiment provides a bone cement, which is mainly made of the following raw materials: a powder phase and a liquid phase, wherein the powder phase includes the developer provided in Example 1, and the mass volume ratio of the powder phase to the liquid phase is 2.0 g: 1 mL;
[0106] Based on the weight of the powder phase being 100%, the powder phase includes the following components in weight fractions: 88.5% of polymethyl methacrylate, 0.6% of benzoyl peroxide and 11.0% of a developer;
[0107] Based on the weight of the liquid phase being 100%, the liquid phase includes the following components in mass fractions: 97.49% of methyl methacrylate, 2.5% of N,N-dimethyl-p-toluidine and 0.01% of hydroquinone.
[0108] Examples 11-17
[0109] Examples 11-17 respectively provide a bone cement, which respectively includes the developer provided by Examples 2-8, and the remaining raw materials and amounts are the same as those of Example 10.
[0110] Embodiment 18
[0111] This embodiment provides a bone cement, which is mainly made of the following raw materials: a powder phase and a liquid phase, wherein the powder phase includes the developer provided in Example 9, and the mass volume ratio of the powder phase to the liquid phase is 2.2g:1mL;
[0112] Based on the weight of the powder phase being 100%, the powder phase includes the following components in weight fractions: 90.5% of polymethyl methacrylate, 0.5% of benzoyl peroxide and 9.0% of a developer;
[0113] Based on the weight of the liquid phase being 100%, the liquid phase includes the following components in mass fractions: 96.491% of methyl methacrylate, 3.5% of N,N-dimethyl-p-toluidine and 0.009% of hydroquinone.
[0114] The preparation method of bone cement provided in Examples 10-18 comprises the following steps:
[0115] The powder phase and the liquid phase are mixed and solidified to obtain bone cement.
[0116] Comparative Example 1
[0117] This comparative example provides an existing developer barium sulfate for bone cement.
[0118] Comparative Example 2
[0119] This comparative example provides an existing developer iohexol for bone cement.
[0120] Comparative Example 3
[0121] This comparative example provides an existing developer iopamidol for bone cement.
[0122] Comparative Example 4
[0123] This comparative example provides an existing developer for bone cement, which includes ioversol and iobitrol, and the molar ratio of ioversol to iobitrol is 1:1.
[0124] Comparative Example 5
[0125] This comparative example provides a developer for bone cement. Except that the raw material carboxylated graphene in the developer is replaced by graphene, the other raw material types, amounts and preparation methods are the same as those in Example 1.
[0126] Comparative Example 6
[0127] This comparative example provides a developer for bone cement, except that the molar ratio of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent in the developer is replaced by 8:0.1:0.3:1.0, while the other raw material types, amounts and preparation methods are the same as those in Example 1.
[0128] Comparative Example 7
[0129] This comparative example provides a developer for bone cement, except that the molar ratio of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent in the developer is replaced by 9:0.05:0.3:1.0, and the other raw material types, amounts and preparation methods are the same as those in Example 1.
[0130] Comparative Example 8
[0131] This comparative example provides a developer for bone cement, except that the molar ratio of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent in the developer is replaced by 11:0.1:0.3:1.0, and the other raw material types, amounts and preparation methods are the same as those in Example 1.
[0132] Comparative Example 9
[0133] This comparative example provides a developer for bone cement, except that the molar ratio of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent in the developer is replaced by 9:3:0.3:1.0, and the other raw material types, amounts and preparation methods are the same as those in Example 1.
[0134] Comparative Examples 10-18
[0135] This comparative example provides a bone cement, except that the developer is the developer provided by comparative examples 1-9, and the other raw materials and amounts are the same as those in Example 10.
[0136] In order to verify the technical effects of the embodiments and comparative examples, the following experiments were conducted.
[0137] Experimental Example 1
[0138] The compressive strength, flexural strength, flexural modulus and other properties of the bone cement provided in Examples 10-18 and Comparative Examples 10-18 were tested, and the corresponding mechanical properties tests were performed according to the method of Standard YY0459-2003:
[0139] Compression strength test: Mix a set of bone cement powder and liquid under (23±1)℃ environment. When the mixed bone cement is in dough form, carefully fill it into a specific mold to prepare a 6×12mm sample column. Soak the test sample in acidic buffer for 10 days and then place it on the static compression test device of the test equipment. Start the test machine to apply load to the sample at a constant crosshead rate within the range of 19.8mm / min to 25.6mm / min. Stop when the sample breaks or has passed the upper yield point.
[0140] Flexural strength and flexural modulus test: Mix a set of bone cement powder and liquid under (23±1)℃ environmental conditions. When the mixed bone cement is in a dough-like state, carefully fill it into a specific mold to prepare a 75×10×3.3mm specimen. After soaking the test specimen in an acidic buffer for 10 days, place it on the test equipment device. Use a bending tester to apply force on the central load column from zero at a crosshead rate of 5mm / min±1mm / min, record the change of the test strip deflection with the applied force, and continue to apply force until the test strip breaks. The specific results are shown in Table 1.
[0141] Table 1:
[0142]
[0143]
[0144] It can be seen from the above table that the mechanical properties of the bone cement (Examples 10 to 18) prepared using the bone cement developer of the present application are not significantly different from those of the existing bone cement (Comparative Example 10) (p>0.05), which proves that replacing the traditional bone cement developer with the bone cement developer of the present application will not affect the mechanical properties of bone cement.
[0145] The mechanical properties of the bone cement prepared in Comparative Examples 11 to 18 were statistically analyzed and showed significant differences (p < 0.05) compared with the existing bone cement (Comparative Example 10), proving that the changes in the ratios of carboxylated graphene, iodine alcohol compounds, catalysts and dehydrating agents in the developer have a significant effect on the mechanical properties of bone cement. However, in order to ensure the safety and effectiveness of the clinical application of bone cement, the mechanical properties should be close to those of existing bone cement and should not be too high or too low. According to this test example, the bone cement prepared in Examples 10 to 18 of the present application is closer to the mechanical properties of existing bone cement than the bone cement prepared in Comparative Examples 11 to 18. Therefore, the bone cement prepared in Examples 10 to 18 of the present application can better meet clinical application needs.
[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A developer for bone cement, characterized in that: It has a graphene-iodine alcohol composite structure and is mainly made of the following raw materials; Carboxylated graphene, iodine alcohol compounds, catalysts and dehydrating agents; The molar ratio of carboxylated graphene, iodine alcohol compound, catalyst and dehydrating agent is (9-10): (0.1-2.5): (0.3-0.6): (1.0-1.5).
2. The developer for bone cement according to claim 1, characterized in that: The iodine alcohol compound includes any one of iohexol, iopamidol, ioversol, iobitrol or iodixanol, or a combination of at least two thereof; Preferably, the carboxylated graphene has a thickness of 1-5 nm and a diameter of 1-3 um.
3. The developer for bone cement according to claim 1 or 2, characterized in that: The dehydrating agent includes N,N'-dicyclohexylcarbodiimide and / or 1-ethyl-3 (3-dimethylpropylamine) carbodiimide; Preferably, the catalyst comprises 4-dimethylaminopyridine or N-hydroxysuccinimide.
4. The method for preparing a developer for bone cement according to any one of claims 1 to 3, characterized in that: The following steps are involved: The carboxylated graphene, the iodine alcohol compound, the catalyst and the dehydrating agent are mixed to carry out an esterification reaction, so as to obtain a developer for bone cement having a graphene-iodine alcohol composite structure.
5. The method for preparing a developer for bone cement according to claim 4, characterized in that: The reaction temperature of the esterification reaction is 20-50°C, and the reaction time is 2-6h; Preferably, the preparation method further comprises the steps of: rinsing the esterification product with deionized water at room temperature after the esterification reaction, and then drying it at 50-60° C. for 2-3 hours.
6. A bone cement, characterized in that: It is mainly made of the following raw materials: a powder phase and a liquid phase; wherein the powder phase comprises the developer for bone cement according to any one of claims 1 to 3; Preferably, based on 100% by weight of the powder phase, the mass fraction of the developer in the powder phase is 9.0-11.0%.
7. The bone cement according to claim 6, characterized in that It is mainly made of the following raw materials: a powder phase and a liquid phase, wherein the mass volume ratio of the powder phase to the liquid phase is 2.0-2.2 g:1 mL; Based on the weight of the powder phase being 100%, the powder phase comprises the following components in mass fractions: 88.5-90.5% of polymethyl methacrylate, 0.4-0.6% of initiator and 9.0-11.0% of developer; Taking the weight of the liquid phase as 100%, the liquid phase comprises the following components in mass fractions: 96.49-97.49% of methyl methacrylate, 2.5-3.5% of an accelerator and 0.009-0.011% of a retarder.
8. The bone cement according to claim 6, characterized in that It is mainly made of the following raw materials: a powder phase and a liquid phase, wherein the mass volume ratio of the powder phase to the liquid phase is 2.0-2.2 g:1 mL; Based on 100% by weight of the powder phase, the powder phase comprises the following components in mass fractions: 88.5-90.5% of polymethyl methacrylate, 0.4-0.6% of benzoyl peroxide and 9.0-11.0% of a developer; Taking the weight of the liquid phase as 100%, the liquid phase comprises the following components in mass fractions: 96.49-97.49% of methyl methacrylate, 2.5-3.5% of N,N-dimethyl-p-toluidine and 0.009-0.011% of hydroquinone.
9. The method for preparing bone cement according to any one of claims 6 to 8, comprising the following steps: The powder phase and the liquid phase are mixed and solidified to obtain bone cement.